Cannabidiol Mediates Beneficial Effects on the Microvasculature of Murine Hearts with Regard to Irradiation-Induced Inflammation and Early Signs of Fibrosis - Lisa Bauer; Bayan Alkotub; Markus Ballmann; Khouloud Hachani; Mengyao Jin; Morteza Hasanzadeh Kafshgari; Gerhard Rammes; Alan Graham Pockley; Gabriele Multhoff (Radiation, 2025)
Objective: Radiotherapy administered to control thoracic cancers results in a partial irradiation of the heart at mean doses up to 19 Gy, which increases the risk of developing a spectrum of cardiovascular diseases known as radiation-induced heart disease (RIHD). As inflammation is a major driver of the development of RIHD, we investigated the potential of the anti-inflammatory agent cannabidiol (CBD) to attenuate irradiation-induced cardiovascular damage in vivo. Methods: Female C57BL/6 mice were given daily injections of CBD (i.p., 20 mg/kg body weight) for 4 weeks beginning either 2 weeks prior to 16 Gy irradiation of the heart or at the time of irradiation. Mice were sacrificed 30 min and 2, 4, and 10 weeks after irradiation to investigate the expression of inflammatory markers and stress proteins in primary cardiac endothelial cells (ECs). DNA double-strand breaks, immune cell infiltration, and signs of fibrosis were studied in explanted heart tissue. Results: We showed that the irradiation-induced upregulation of the inflammatory markers ICAM-1 and MCAM was only attenuated when treatment with CBD was started 2 weeks prior to irradiation but not when the CBD treatment was started concomitant with irradiation of the heart. The protective effect of CBD was associated with a decrease in irradiation-induced DNA damage and an increased expression of protective heat shock proteins (Hsp), such as Hsp32/Heme-oxygenase-1 (HO-1) and Hsp70, in the heart tissue. While the upregulation of the inflammatory markers ICAM-1 and MCAM, expression was prevented up to 10 weeks after irradiation by CBD pre-treatment, and the expression of VCAM-1, which started to increase 10 weeks after irradiation, was further upregulated in CBD pre-treated mice. Despite this finding, 10 weeks after heart irradiation, immune cell infiltration and fibrosis markers of the heart were significantly reduced in CBD pre-treated mice. Conclusion: CBD treatment before irradiation mediates beneficial effects on murine hearts of mice, resulting in a reduction of radiation-induced complications, such as vascular inflammation, immune cell infiltration, and fibrosis.